Mutation Maker, An Open Source Oligo Design Platform for Protein Engineering - Hiraga, Kaori; Mejzlik, Petr; Marcisin, Matej; Vostrosablin, Nikita; Gromek, Anna; Arnold, Jakub; Wiewiora, Sebastian; Svarba, Rastislav; Prihoda, David; Clarova, Kamila; Klempir, Ondrej; Navratil, Josef; et al. (ACS synthetic biology, 2021)
Protein engineering is the discipline of developing useful proteins for applications in research, therapeutic, and industrial processes by modification of naturally occurring proteins or by invention of de novo proteins. Modern protein engineering relies on the ability to rapidly generate and screen diverse libraries of mutant proteins. However, design of mutant libraries is typically hampered by scale and complexity, necessitating development of advanced automation and optimization tools that can improve efficiency and accuracy. At present, automated library design tools are functionally limited or not freely available. To address these issues, we developed Mutation Maker, an open source mutagenic oligo design software for large-scale protein engineering experiments. Mutation Maker is not only specifically tailored to multisite random and directed mutagenesis protocols, but also pioneers bespoke mutagenic oligo design for de novo gene synthesis workflows. Enabled by a novel bundle of orchestrated heuristics, optimization, constraint-satisfaction and backtracking algorithms, Mutation Maker offers a versatile toolbox for gene diversification design at industrial scale. Supported by in silico simulations and compelling experimental validation data, Mutation Maker oligos produce diverse gene libraries at high success rates irrespective of genes or vectors used. Finally, Mutation Maker was created as an extensible platform on the notion that directed evolution techniques will continue to evolve and revolutionize current and future-oriented applications.
Keywords: mutace; Oligonucleotides; oligonukleotidy; Escherichia coli; počítačová simulace; mutageneze; mutageneze cílená; software; kodon; Mutation; řízená evoluce molekul; Proteins; Codon; Algorithms; Mutagenesis, Site-Directed; Computer Simulation; Mutant Proteins; proteiny; genová knihovna; Mutagenesis; Gene Library; mutantní proteiny; algoritmy; Software; Directed Molecular Evolution